ECOM ZONABIO - Enriquez Chavez, Angela Lourdes (2020)
2020 has been a year without precedents, Covid 19 has revolutionized the ways of doing business, this is how we see the greatest acceleration in the use of information technologies worldwide and also a better use of emerging technologies such as: Cloud-based Artificial intelligence, Machine learning, IoT, Advanced analytics, Digital ecosystems, Augmented reality, etc. Although it is true that we already had online stores such as Amazon, Linio, Alibaba, etc. The current situation forces us to take a 180 degree turn in terms of electronic commerce, because currently companies and entrepreneurs that promote products and services use recommendation systems, through the use of intelligent algorithms - Machine Learning, as a sales growth strategy which allows them a better customer orientation in regard their products in different business sectors. For Peru, it is a great opportunity to implement a green and smart recommendation system for organic products, because currently there are no online businesses with that classification of recommendation systems. Its implementation will have a positive impact, guiding customers to acquire a healthy lifestyle, improving quality of life for consumers, and increasing entrepreneurs sales. According to WHO (2020) a healthy diet is very important during the COVID-19 pandemic. What we eat and drink can affect our bodies' ability to prevent, fight and recover from infections. For this reason, there is a growing trend towards the consumption of organic products according to people's lifestyles all over the world. Our creation is an innovative product called ECOM ZONABIO that is easy to view in different devices such as: laptops, tablets, smartphones etc.; whose differentiation is in the recommendation algorithms, allowing ecological bloggers to expand their online presence more quickly for a better diffusion of organic products. Our solution will also allow our consumers to obtain information on products and customers who have similar interests or expectations, as well as a great experience when looking for an organic product for purchase, customers will not have to have prior knowledge of advanced information technologies as a requirement to interoperate with the ECOM ZONABIO platform.